ERNESTO GUEVARA IDEALISTA, REVOLUCIONARIO Y HUMANO That was Che, an example of doctor, revolutionary and warrior - Ariadna Rendueles (Universidad de Ciencias Médicas de La Habana, 2008)
During his studies in the MedicineSchool, Ernesto Guevara de la Serna, starts a long trip through Latin America. This sets a precedent in his formation as a doctor. He finally arrives to Buenos Aires in August 31st 1952; where he receives a certification as a doctor after he evaluates all the missing subjects. “In Guatemala I want to acquire perfection as an authentic revolutionary” Mario Salazar Mallén. (9) At the beginning of 1955 “Che” finds job as a doctor in the Central Hospital of Mexico City . Fidel said: “When we met, “Che” was an educated revolutionary” Ernesto meets Ñico López in 1955, through him, he meets Raul and this one introduces him to Fidel. In June 24, 1956, Che is made prisionera long with other cuban comrades. At the end of July, among the lasts , Che is released. Revolution, medicine and society The medical thought of Ernesto Guevara was evident in articles, books and speeches since he started to work as a health professional. He understands the need of the integration of the doctor inside the revolutionary process. Guevara adds to the radical changes of the doctor in health in the new society : being a farmer, to know about the cultivation of new alimentsand the promotion of a new diverse alimentationutilizing the advantages of a country that is mainly agricultural . The doctor must keep being a doctor, but as a revolutionary. That was Che, an example of doctor, revolutionary and warrior.